Pain predictability reverses valence ratings of a relief-associated stimulus - Andreatta, Marta; Mühlberger, Andreas; Glotzbach-Schoon, Evelyn; Pauli, Paul (Frontiers in Systems Neuroscience, 2013)
Relief from pain is positively valenced and entails reward-like properties. Notably, stimuli that became associated with pain relief elicit reward-like implicit responses too, but are explicitly evaluated by humans as aversive. Since the unpredictability of pain makes pain more aversive, this study examined the hypotheses that the predictability of pain also modulates the valence of relief-associated stimuli. In two studies, we presented one conditioned stimulus (FORWARDCS+) before a painful unconditioned stimulus (US), another stimulus (BACKWARDCS+) after the painful US, and a third stimulus (CS-) was never associated with the US. In Study 1, FORWARDCS+ predicted half of the USs while the other half was delivered unwarned and followed by BACKWARDCS+. In Study2, all USs were predicted by FORWARDCS+ and followed by BACKWARDCS+. In Study1 both FORWARDCS+ and BACKWARDCS+ were rated as negatively valenced and high arousing after conditioning, while BACKWARDCS+ in Study 2 acquired positive valence and low arousal. Startle amplitude was significantly attenuated to BACKWARDCS+ compared to FORWARDCS+ in Study2, but did not differ among CSs in Study1. In summary, predictability of aversive events reverses the explicit valence of a relief-associated stimulus.